1970
DOI: 10.3329/ptcb.v17i2.3237
|View full text |Cite
|
Sign up to set email alerts
|

Novel ESTs from a Jute (Corchorus olitorius L.) cDNA Library

Abstract: The paper describes the identification of new expressed sequence tags (ESTs) from a cDNA library of Corchorus olitorius L. var. O-4 after the initial description of the library construction reported recently. The sequence homology search in The Arabidopsis Information Source (TAIR) using the WU-BLAST tool revealed four complete and ten partial cDNA sequences. The complete cDNA sequences, based on their similarities to those of Arabidopsis proteins, encode V-ATPase subunit F, mitochondrial NADH-ubiquinone oxido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Moreover, our study indicated unigenes of C. capsularis have highest homology to P. trichocarpa, and which also have higher homology to R. communis, C. olitorius and V. vinifera. The results are different with Wazni et al, who reported the homology was maximum between black jute (olitorius) and cotton followed by citrus, grapevine, tobacco and arabidopsis (Wazni et al, 2007), which illustrates the differences between black and white jute. Above results would be a potential resource for comprehensive genomic studies in Corchurus species.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Moreover, our study indicated unigenes of C. capsularis have highest homology to P. trichocarpa, and which also have higher homology to R. communis, C. olitorius and V. vinifera. The results are different with Wazni et al, who reported the homology was maximum between black jute (olitorius) and cotton followed by citrus, grapevine, tobacco and arabidopsis (Wazni et al, 2007), which illustrates the differences between black and white jute. Above results would be a potential resource for comprehensive genomic studies in Corchurus species.…”
Section: Discussioncontrasting
confidence: 88%
“…Jute fibres exhibit a characteristically high luster, good moisture absorption performance, rapid water loss capacity and easy degradation (Zhang et al, 2013). The textile and paper industry are interested in its potential as an important ingredient for producing paper, fine textiles as well as a renewable source for biofuel (Wazni et al, 2007). In recent years, with increasing uses of jute in diversified industries, there is a growing demand for highyielding new cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Jute is important for the textile and paper industries because it is a valuable ingredient for the production of paper and Determining genetic diversity of deshi jute (Corchorus capsularis) for the improvement of fibre yield and associated traits quality textiles as well as a renewable source of biofuels [10]. Jute fibers characteristically show high gloss, good moisture absorption performance, rapid dehydration capacity and easy degradation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable nature of jute fiber and the potential high yield of cellulose biomass per acre have increased the global interest in jute. Textile and paper industries are also interested in its potential as an important ingredient for producing paper and fine textiles14. As with other lignocellulosic plants the drawback of jute when used as a source for such purposes is the abundance of lignin polymer that renders the plant material almost inaccessible for downstream processes.…”
mentioning
confidence: 99%